Short-term impacts of the filling transition across elevations in intermittent water supply systems - Weston, S.L.; Loubser, C.; Jacobs, H.E.; Speight, V. (Urban water journal, 2023)
Intermittent Water Supply (IWS) is characterised as drinking water distribution systems that are supplied with water for less than 24 hours/day on average. The filling transition from non-supply to pressurised supply is a period of hydraulic instability that negatively impacts water quality, deteriorates infrastructure integrity and intensifies social inequalities. Understanding the factors contributing to the severity of impact from filling is vital to develop effective management strategies. This paper investigates the hydraulic phenomena induced during the short-term IWS filling period and how this behaviour can be exacerbated by elevation and other hydraulic system factors, such as velocity and pressure. Controlled laboratory experiments conducted in the UK and field studies performed in operational networks across South Africa are presented. Results demonstrate the crucial role elevation plays in the network response during the filling transition, emphasising the need for greater consideration of elevation in IWS and well-maintained air relief valves in strategic locations.